(untitled) (Eurasian Scientific Herald, 2023)
The article examines the role of e-commerce in the modern economy. The role of modern electronic commerce is becoming one of the most important for the future prosperity of the entire economy in an ever-evolving world. The article discusses the essence of ecommerce, an analysis of the dynamics of the global online trading market, and also provides key trends in the development of e-commerce. However, the largest contributors to the global e-commerce market are still predominantly made by American and Chinese companies. The article examines the current state of the global e-commerce market, as well as the main strategies of global companies, the role of e-commerce and the prospects for the economy of Central Asia. Based on the research conducted, appropriate conclusions were drawn reflecting the essence of the article.